Agricultural sustainability promotion: Impact on rice productivity in Lower Limpopo Irrigation, Gaza, Mozambique - Oldimiro Amaral Leonor Chaúque; António Elísio José; Eugenio da Piedade Edmundo Sitoe; Bento Filipe Francísco (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2024)
Agricultural promotion seeks to strengthen family farming and boost socio-economic development in vulnerable rural communities. In the Lower Limpopo River (LLR), these initiatives have focused on transforming rice production, which is essential for local livelihoods and socio-economic development. However, the impact of these actions on the productive efficiency and sustainability of the family sector remains poorly explored. This study assessed the impact of agricultural promotion on rice productivity in the family sector of the RBL irrigated area. Data was obtained from a representative sample of 106 family rice producers, considering demographic profiles and diversified agricultural practices. Semi-structured interviews were conducted to analyze indicators such as economic income, job creation, agricultural productivity and cultivation practices. The results indicated a significant improvement in the productive efficiency and income generation of the families. Rice yields increased from 2 to 6 tons per hectare between 2016/2017 and 2020/2021. The number of workers also increased, from 17 temporary workers per hectare in 2016/2017 to 252 temporary workers and 7 permanent workers in 2020/2021. Economic revenue increased significantly, from 65,900.00 MZN (1,032.21 USD) to 91,440.00 MZN (1,432.25 USD) in the same period. The results show the potential of agricultural promotion strategies to transform family farming, promote sustainable development and improve the living conditions of small farmers. It is recommended that these practices be expanded and that public policies be implemented to ensure their long-term sustainability.